A contribuição das práticas de experimentotecas em solos na Escola Municipal de Ensino Fundamental Euclides da Cunha, Santa Maria-RS - Saldanha, Cibele Stefanno (2019)
School Geography needs to appropriate didactic resources and methodologies consonant with contemporaneity, integrating experimental methods to the educational process. The environmental theme is strongly marked in its discourse, needing to pass through advances in relation to didactic resources and, in this context, the soil is an essential resource for the functioning of ecosystems, however it is not recognized as it should be so little worked in the Schools. The present study aims to develop and practice experimenters in soils and to verify their effectiveness as a teaching and learning instrument in the discipline of Geography and to evaluate how students learn the subject through textbooks and interview with the titular teacher of the discipline, and The experimenters sought to demonstrate experiments with an emphasis on the following morphological aspects: Soil color analysis, soil texture, soil consistency, and soil composition. soil porosity, thus facilitating the teaching and learning of learners through the sensory system, we sought to achieve meaningful learning and collaborate with the perception of the importance of soil study in the environmental context. Sixyear-olds were investigated through questionnaires and observations carried out along experiment-library practices and perceptions, and it was concluded that experimenter's practices were widely accepted by the students and contributed in fact to soil education in Geography, however the theme soils has been insufficiently developed in textbooks and is being exposed in the classroom in an unsatisfactory way.